Genetic foundations of pathbiochemical peculiarities of connecting tissue of patients with prolapsis of genitals - M L Khanzadyan; V E Radzinsky (IP Berlin A.V., 2017)
Purpose: to study the molecular biological basis of genital prolapse, its determination by the carrier of polymorphisms of laminin, collagen, estrogen receptor and vascular endothelial growth factor. Materials and methods: 178 women aged 35-65 years were examined, 134 of them with relapses of prolapse genital (PG) after hysterectomy with vaginal access due to complete and incomplete prolapse of the uterus and vaginal walls were randomized into groups: 1 - with manifestations of undifferentiated connective dysplasia tissue (DST), 11.7 points on average (n=86); 2 - without signs of DST (n=48). The control group 3 consisted of healthy women without signs of PG (n=44). The morphological method of investigation along with the immunohistochemical method was used to evaluate the biopsy specimens of the uterosacral ligaments (USL) and round ligaments of the uterus (RLU), the genotyping by polymerase chain reaction of polymorphisms LAMC1 3054 C>T, COL3A1 2092 (2209) G>A, ESR1 351 G>A [XbaI], VEGFA 634 G>C with isolation of DNA samples from whole blood. Results: morphological features of the structural components of the USL and RLU were realized in the predominance of excessive fibrosis of the connective tissue on the background of disunity and loosening of collagen fibers and myocyte dystrophy. Expressed dysplastic changes with loss of elasticity of fibers due to increased fragmentation of elastin, excessive synthesis of the least strong type III collagen in comparison with type I, perivascular edema were traced in the group with signs of DST (in 65% of women). The decrease in tissue strength in the imbalance of synthesis and degradation of collagens in patients with PG was correlated with the excess production of type III protein - high in USL and moderate - in RLU. Healthy women were distinguished by the prevalence of type I collagen (5.5 and 4.2 points respectively) - one and a half times more than in pelvic descent (3.2 and 2.7 points respectively). The increased degradation of elastic fibers in PG determined the fragmentarity of their distribution in the ligamentous apparatus of the uterus in comparison with the uniform one - along the collagen fibers, in the extracellular matrix and fibroblasts, the walls of the arterioles of the USL and RLU in healthy women. The genetic determinateness of molecular-biological features of connective tissue structures with PG is determined, which allows to predict the risk of the disease development at the preclinical stage. The carriage of "risky" alleles of the genes COL3A1 2092 (2209) G>A (rs1800255) (45.8% vs 29.5%) in the presence of DST manifestations indicated associativity with PG. The frequency of the allele GC of the VEGFA gene with PG was equally increased: in the absence of signs of DST - by one and a half times (59.3% vs 36.4%, p=0.002, OR=9.9, 95% CI 1.6-7.6), in the presence of collagenopathies - in two (35.4% versus 15.9%, p=0.01, OR=2.9, 95% CI, 1.1-6.9) with a comparable occurrence of heterozygotes (36.9% on average). The absence of associative links was established for laminin LAMC1 (connective tissue) (50% versus 31.8%) and estrogen receptor ESR1 -351 G> A [XbaI] (43.4%). Representatives with collagenopathies distinguished the high carrier burden of the mutant polymorphism rs3918242 - twice as much compared to the control group (35.4% vs 15.9%, p=0.01, OR=2.9, 95% CI 1.1-6.9) with a comparable occurrence of heterozygotes (36.9% on average). The conclusion. The determinism of pathobiochemical features of connective tissue is revealed - the imbalance of synthesis and degradation of its components, the formation of an abnormal structure of fibers and the expressed polymorphism of polymorphisms of genes that control the safety of tissue architectonics of the pelvic ligaments. Expansion of PG prediction capabilities is most likely in the presence of signs of DST predetermining the systemic nature of its lesion and variety of symptoms, with a particular manifestation in the form of pelvic floor insufficiency in the presence of "risky" polymorphisms of the genes LAMC, COL3A1 and VEGFA. Determination of genes predisposing to PG allows us to formulate the concept of its pathogenesis, with the identification of risk groups not only of development, but also the relapse of the disease after surgery, by choosing the most optimal method of surgical correction.